A Carrying Capacity Calculator for Pedestrians Using OpenStreetMap Data: Application to Urban Tourism and Public Spaces - Sampaio de Almeida, D.; Simões, R.; Brito e Abreu, F.; Lopes, A.; Inês Boavida-Portugal (Proceedings of ENTER 2025 International eTourism Conference, 2025)
Determining the carrying capacity of urban tourism destinations and public spaces is essential for sustainable management. This paper presents an online tool that calculates pedestrian carrying capacities for user-defined areas based on OpenStreetMap (OSM) data. The tool considers physical, real, and effective carrying capacities by incorporating parameters such as area per pedestrian, rotation factor, corrective factors, and management capacity. The carrying capacity calculator aids in balancing environmental, economic, social, and experiential factors to prevent overcrowding and preserve the quality of life for residents and visitors. This tool can be used for tourism destination management, urban planning, and event management to ensure positive visitor experiences and sustainable infrastructure development. We detail the implementation of the calculator, its underlying algorithm, and its application to the Santa Maria Maior parish in Lisbon, highlighting its effectiveness in managing urban tourism and public spaces.